2015
DOI: 10.1186/s12931-015-0216-4
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac safety of tiotropium in patients with cardiac events: a retrospective analysis of the UPLIFT® trial

Abstract: BackgroundTiotropium is an anticholinergic bronchodilator for symptom relief and reducing exacerbations with an established safety profile in patients with chronic obstructive pulmonary disease (COPD). Using data from the 4-year Understanding Potential Long-term Impacts on Function with Tiotropium (UPLIFT®) study, we re-evaluated the safety of tiotropium HandiHaler® in patients who experienced recent myocardial infarction (MI), heart failure or unstable rhythm disorder during the study.MethodsA post-hoc analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 24 publications
0
34
0
7
Order By: Relevance
“…Similarly, the cardiac safety of inhaled antimuscarinic agents has been debated for more than a decade (17,100). Short-acting bronchodilators, such as ipratropium, may slightly increase the risk of HF (101), whereas there seems to be no additional risk of incident HF due to tiotropium use (102,103) or with newer long-acting antimuscarinic antagonists (LAMAs) (i.e., glycopyrronium [104], aclidinium [105], and umeclidinium [106]) or even with the LABA/LAMA combination indacaterol/glycopyrronium (107).…”
Section: Treatment Of Copd In Patients Withmentioning
confidence: 99%
“…Similarly, the cardiac safety of inhaled antimuscarinic agents has been debated for more than a decade (17,100). Short-acting bronchodilators, such as ipratropium, may slightly increase the risk of HF (101), whereas there seems to be no additional risk of incident HF due to tiotropium use (102,103) or with newer long-acting antimuscarinic antagonists (LAMAs) (i.e., glycopyrronium [104], aclidinium [105], and umeclidinium [106]) or even with the LABA/LAMA combination indacaterol/glycopyrronium (107).…”
Section: Treatment Of Copd In Patients Withmentioning
confidence: 99%
“…Increased mortality was noted with inhaled tiotropium via the Respimat device,34 although a study in 17,135 people with a mean follow-up of 2.3 years found tiotropium delivered by Respimat to be non-inferior to tiotropium delivered by Handihaler with respect to the risk of death 35. Post-hoc analysis of data from the 4-year UPLIFT study reported no excess of deaths or serious cardiac events in people receiving tiotropium via the Handihaler compared with placebo 36. Patients treated with tiotropium were not found to be at increased risk of cardiac events compared with placebo.…”
Section: Safety Issues With Lama/labasmentioning
confidence: 99%
“…A prevenção das exacerbações com tiotrópio em pacientes com DPOC apresentou um excesso de eventos isquêmicos coronários graves com o tiotrópio em comparação com o salmeterol. Os autores recomendam cautela na prescrição de anticolinérgicos inalados para pacientes com arritmias pré-existentes ou doenças cardíacas [16][17][18] . Concluímos que a prescrição de medicamentos como os antimuscarínicos é um item importante para a reabilitação pulmonar em pacientes com DPOC porque melhoram os sintomas, particularmente a dispneia e a capacidade de fazer as atividades diárias.…”
Section: Efeitos Colaterais Dos Medicamentos Anticolinérgicosunclassified